2022
DOI: 10.3390/life12030460
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Management and Treatment of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a priority health problem with a high cost to society and a large consumption of medical and social resources. The management of AD patients is complex and multidisciplinary. Over 90% of patients suffer from concomitant diseases and require personalized therapeutic regimens to reduce adverse drug reactions (ADRs), drug–drug interactions (DDIs), and unnecessary costs. Men and women show substantial differences in their AD-related phenotypes. Genomic, epigenetic, neuroimaging, and bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 180 publications
(307 reference statements)
0
7
0
Order By: Relevance
“…The G2 (up-down) also includes proteins located on multiple known AD-risk loci such as SPI1 and Protein Tyrosine Kinase 2 Beta (PTK2B), as well as other proteins known to be implicated on AD or neurodegeneration such as Brain-Derived Neurotrophic Factor (BDNF) 37 , 38 , Cathepsin D (CTSD) 39 , 40 , and Nuclear Factor Kappa B Subunit 1 (NFKB1) 41 , 42 . Some of the key proteins contained in the G3 (linear decrease) group include Carboxylesterase 1 (CES1) 43 , Interleukin 6 (IL6) 44 , 45 , and Forkhead Box O1 (FOXO1) 46 , 47 , which have been implicated in various metabolic, age-, and immune system-related mechanisms that underlie AD pathogenesis. Finally, and consistent with previous study, 48 we found Triggering Receptor Expressed On Myeloid Cells 2 (TREM2) in the G4 (down-up), which showed a decrease from controls to the asymptomatic stage but then significantly elevated levels are noticed in AD individuals.…”
Section: Resultsmentioning
confidence: 99%
“…The G2 (up-down) also includes proteins located on multiple known AD-risk loci such as SPI1 and Protein Tyrosine Kinase 2 Beta (PTK2B), as well as other proteins known to be implicated on AD or neurodegeneration such as Brain-Derived Neurotrophic Factor (BDNF) 37 , 38 , Cathepsin D (CTSD) 39 , 40 , and Nuclear Factor Kappa B Subunit 1 (NFKB1) 41 , 42 . Some of the key proteins contained in the G3 (linear decrease) group include Carboxylesterase 1 (CES1) 43 , Interleukin 6 (IL6) 44 , 45 , and Forkhead Box O1 (FOXO1) 46 , 47 , which have been implicated in various metabolic, age-, and immune system-related mechanisms that underlie AD pathogenesis. Finally, and consistent with previous study, 48 we found Triggering Receptor Expressed On Myeloid Cells 2 (TREM2) in the G4 (down-up), which showed a decrease from controls to the asymptomatic stage but then significantly elevated levels are noticed in AD individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Succeeding in this, the electrical correlate of altered neuron membrane excitability due to ion channel dysregulation, as already effectively proposed as a putative target/marker of the disease [ 18 , 19 , 20 , 37 ], could be extended at the NPC-Nup-NCT machinery level. Accordingly, our future goals will comprise the developing of ion channel-targeted neurotherapies based on the Nup pathogenetic cascade, according to modern pharmacogenetics and personalized pharmacology guidelines [ 38 , 39 ] established for neurological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of neuropsychiatric disorders is increasing day by day, 293 but there are limitations in diagnosis, 294 , 295 limited means of treatment, and unsafe drugs. 296 , 297 , 298 Naturally derived biological humoral exosomes possess specific biomolecules that can be used as a “signature” of parent cells to reflect changes in their contents under pathological conditions. The occurrence and pathophysiological mechanism of the disease can be understood by detecting its changing contents.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%